INFLUENCING THE INDENTATION CURVES BY THE BLUNTNESS OF THE BERKOVICH INDENTER AT THE FEM MODELLING - Jaroslav Kovář (Acta Polytechnica CTU Proceedings, 2020)
The influence of the Berkovich indenter bluntness on the indentation curves at nanoindentation test of fused silica is determined by the FEM (finite element method) in this paper. The Berkovich indenter, which is mostly used for the nanoindentation test, was assumed for calculations. The indenter is always blunted in real tests. The bluntness of the indenter has an influence on the results of the nanoindentation test. The combination of the nanoindentation test and the FE modelling can be used for the calculation of the parameters of fused silica plasticity and estimation of the bluntness of the indenter. In this paper, the FEM was used for calculating of the indentation curves. Two cases of bluntness were assumed. The curves for ideally sharp or blunted indenter were determined. The results of these calculations showed that the indentation curves are dependent on the bluntness of the Berkovich indenter. The greatest relative influence of the nanoindentation curves by the bluntness is in the area of small values of the indenter displacement. The impact of assuming blunted indenter to calculated parameters of plasticity was assessed. It is often difficult to measure the bluntness of the indenter but it has an influence on the results of the nanoindentation test and should be included into calculations to make it more precise.